CompTIA Network+ CertMike prepare, practice, pass the test! get certified! exam N10-008 - Chapple, Mike; Zacker, Craig (Sybex Inc, 2023)
A laser-focused and job-ready blueprint for success on the CompTIA Network+ exam and a running start on your first (or next) job in tech CompTIA Network+ CertMike: Prepare. Practice. Pass the Test! Get Certified! Exam N10-008 delivers a no-nonsense, straight-to-business guide to acing the CompTIA Network+ test on your first attempt. Veteran tech experts and educators Mike Chapple and Craig Zacker walk you through every step you'll need to take on the N10-008 exam, from networking fundamentals, implementations, and operations to network security and troubleshooting. Ace the test using the proven CertMike approach: Prepare -- CertMike is your personal study coach, guiding you through all the exam objectives and helping you gain an understanding of how they apply to on-the-job tasks! Practice -- Each chapter includes two multiple choice practice questions. Work through the detailed explanations to evaluate each answer option and understand the reason for the best answer! Pass -- On exam day, use the critical knowledge you've learned when you're ready to take the test. You'll feel ready and confident to pass the exam and earn your certification! The book skips the fluff and gets right to the point of getting you familiar with network basics and on the road to an in-demand certification and a new career as a network technician or admin. You'll also get complimentary access to additional Sybex online study tools, including a bonus practice exam and audio recordings of the book's CertMike Exam Essentials. A can't-miss roadmap to success on the Network+ exam, CompTIA Network+ CertMike: Prepare. Practice. Pass the Test! Get Certified! Exam N10-008 is the job-focused and practical guide you've been looking for to help you hone your networking skills.
Keywords: Computer networks -- Study guides -- Examinations; Electronic data processing personnel -- Certification; Réseaux d'ordinateurs; Examens; Guides de l'étudiant; Computer networks; Examinations; Electronic data processing personnel; Certification; Study guides